Regional tourism at the farmers' market: consumers' preferences for local food products. Issue 1 (24th May 2019) - Garner, Benjamin; Ayala, Cesar
Abstract : Purpose: The purpose of this paper is to examine farmers' market consumer behavior through a regional food and culinary tourism lens to see the ways these festive and atmospheric markets can be used to develop a regional brand or identity surrounding food production. Design/methodology/approach: This study was based on a survey of 270 participants in a farmers' market in the USA. A combination of descriptive and statistical analyses was used to analyze consumer habits and spending. Findings: The findings in this study suggest that while most of the customers live in a town where the market is located, a significant number of customers come from other locations, with some traveling significant distances, to participate in this market, particularly for the Saturday market. Many of the customers come to purchase organic and local foods. Research limitations/implications: This work is limited, in that it is a case study at one farmers' market in the USA, and the work is exploratory in nature. Practical implications: This work has implications for market managers seeking to increase their consumer base. Markets that want to increase their reach would do well to promote their events to a wider geographic area. The results presented here showed that consumers are willing to drive upward of 40 miles to attend a high-quality market. Originality/value: This work expands our conceptualization of farmers' markets by suggesting that these markets have the potential to form the backbone of a region is food identity through the creation of a food destination.